The importance of nutrition for control autoimmune diseases (Research, Society and Development, 2024)
Studies suggest that autoimmune diseases are caused by a lack of control in the immune system and that their development is related to multifactorial factors, such as genetic and environmental. The relationship between nutrition and systemic immune responses has attracted considerable attention as a strategy for controlling autoimmune diseases. In view of the above, this work aimed to verify the effect of nutritional therapy on the control of immunosuppressive chronic inflammations, based on a literature review, academic works, magazines with the work theme and scientific bases such as ScienceDirect, PubMed, MDPI were used, considering articles published between 2009 - 2024, in Portuguese and English, excluding those that prioritized physical exercise, drugs or other treatments that were not related to food and nutrition.  The health and proper functioning of the intestinal microbiota, a specific diet that can improve the inflammatory symptoms of immunosuppressive diseases, supplementation with omega 3 fatty acids, vitamin D, C and zinc can bring benefits to immunity and improve the symptoms of the pathology.